Urutan pemerolehan Al-ḍamīr dalam ayat nominatif bahasa Arab dalam kalangan pelajar institusi pengajian tinggi / Ummi Syarah Ismail, Nazri Atoh and Abdul Basir Awang - Ismail, Ummi Syarah; Atoh, Nazri; Awang, Abdul Basir (2018)
Al-ḍamīr in the nominative sentence of Arabic language is very important in learning its grammar. Al-ḍamīr and nominative sentences are learned in the early stage as the basic level in learning Arabic language. The aim of this study is to identify the sequence of al-ḍamīr and its acquisition in Arabic nominative sentences based on the category of munfaṣil and muttaṣil and also to identify the sequences of al-ḍamīr acquisition from the number of mufrad, muthannā and jamak aspects. The meaning of this sequence is the sequence of al-ḍamīr in highly used to rarely used. The highly used means that it is easy to use while the rarely used means it is difficult to use. This study uses descriptive analysis design with IBM SPSS statistic software. Test sentences were given to 183 students who took Arabic 3 at UiTM Perlis using a purposive sampling. The findings showed that there are highly used and rarely used al-ḍamīr acquisition sequences of students. Based on this acquisition order, students are more easy to use ḍamā‘ir raf' munfaṣilat in the construction of nominative compared to ḍamāīr jar muttaṣilat and ḍamā‘ir naṣb muttaṣilat. While in the numbers aspect, students feel easier